Fundamental fluid mechanics for the practicing engineer - Murdock, James W. (Mechanical engineering (Marcel Dekker, Inc.), 1993)
A step-by-step guide, containing tutorial examples that serve as models for all concepts presented. This text contains properties of nearly 50 fluids, including density and viscosity data for compressed water and superheated steam, and characteristics of areas, pipes and tubing.